Predictors of asthma control among Libyan adolescents with persistent asthma - Elfeturi Elarusy, Nadya Mohamed; Mohd Tamrin, Shamsul Bahri; Sann, Lye Munn; Ismail, Siti Irma Fadhillah (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: Among adolescents, asthma is an important public health burden that is associated with high morbidity and mortality. Poor asthma control is likely in this age group. Our aim was to identify the predictors of well controlled asthma among adolescents with persistent asthma in Northwest of Libya. Methods: A sample of 92 adolescents with persistent asthma were recruited from the respiratory clinic in Sabratha Teaching Hospital, and completed questionnaires measuring demographic and clinical characteristics, asthma knowledge, self-efficacy, and asthma control. Logistic regression analysis was carried out, taking the asthma control as the dependent variable. Results: Twenty-four percent of participants had well controlled asthma. In a bivariate analysis, well controlled asthma was significantly associated with adolescents having mild persistent asthma, not having allergic rhinitis, using preventive inhalers regularly, reporting higher level asthma knowledge, and higher self-efficacy. However, in multiple logistic model, only self-efficacy was an independent predictor of asthma control, with higher self-efficacy associated with well-controlled asthma (Adjusted OR= 1.107, 95% CI: 1.012 – 1.210, p= 0.026). Conclusion: Identifying and targeting modifiable predictors of well controlled asthma could improve asthma control. In adolescents with asthma, enhancing self-confidence of adolescents to undertake health behaviour modification seems to be an important step toward a better asthma control.